Anteseden Employee Performance Mediated by Motivation in Employees in Manufacturing Companies - Kristanti, Brigita; Berliyanti, Dita Oki; Nilasari, B. Medina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the growing dynamics of global business, many companies are innovating products and services to survive and compete in the market. This study aims to analyze the role of Motivation in mediating the influence of Organizational Culture and Transformational Leadership on Employee Performance of employees in Manufacturing Companies. This study uses a Quantitative approach with a non-probability research sample method, namely employees in manufacturing companies in DKI Jakarta and Banten as many as 208 respondents. The independent variables in this study are Organizational Culture and Transformational Leadership, the intervening variable is Motivation, and the dependent variable is Employee Performance. Analysis of this research method using Amos and SPSS applications, by conducting the Sobel Test. The results show that Motivation can partially mediate the effect of Organizational Culture on Employee Performance in Manufacturing companies in DKI Jakarta and Banten, but has not been able to mediate the effect of Transformational Leadership on Employee Performance in Manufacturing companies in DKI Jakarta and Banten.